THE INTERNET?óÔé¼ÔäóS POTENTIAL IN MOTIVATING STUDENTS TO LEARN ENGLISH USING THE INTERNET RESOURCES THROUGH THE INTERNET-BASED LEARNING - Rahmawati Sukmaningrum (ETERNAL (English Teaching Journal), 2011)
This action research was mainly aimed at increasing students?óÔé¼Ôäó motivation to use theinternet resources in their English learning. The result of the research is intended to provideinformation concerning the issue. In this research, I applied the model of Internet-basedlearning in four classes of Economic Faculty at Muhammadiyah University of Surakarta. Thepopulation of this research consisted of 120 students in 4th semester that enroll the EnglishProgram in UMS Language Center. The sample was taken randomly using purposive randomsampling. Forty students were taken as the sample, especially those who had complete marksfor the whole cycle. The data of this research are in form of; (1) students?óÔé¼Ôäó self-completedquestionnaire, (2) observation and field note, and (3) students?óÔé¼Ôäó tasks. The data wereinterpreted descriptively. All the activities of this research were arranged purposively tomotivate/encourage students to be more active using the internet to enhance their Englishlearning. It was not the within the scope of this research to compare the use of technologywith the more traditional tool (i.e., textbook).Key words: students?óÔé¼Ôäó motivation, internet potential, internet-based learning